ANALISIS FAKTOR-FAKTOR YANGMEMPENGARUHI LUAS PENGUNGKAPAN INFORMASI SUKARELA PADA LAPORAN KEUANGAN TAHUNAN (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di BursaEfek Indonesia Tahun 2011-2013) - Yesi Wulandari; Herry Laksito (Diponegoro Journal of Accounting, 2015)
This study aims to obtain empirical evidence about the influence of ownership structure and board characteristics on voluntary disclosure in the annual reports of existing companies in Indonesia Stock Exchange (ISX) in 2011 -2013. Ownership structure is characterized by managerial ownership, blockholder ownership and government ownership, and board characteristic is characteristic by independent directors, size of directors and skill of directos. Control variabels is leverage, liquidity and profitability. The population of this study is all companies listed in Indonesia Stock Exchange in 2011-2013. The total sample was 88 companies, with three years of observations. So the total sample who checked is 185. Data analysis was performed with the classical assumption and hypothesis testing using linear regression. The results of this study indicate that the factor of leverage, liquidity and profitabilitas significantly influence the voluntary disclosure. Meanwhile, leverage has no significant impact on voluntary disclosure.